Improving Students' Ability to Understand Faith in the Last Day by Using the Problem Based Learning Method at SMP Negeri 3 Trienggadeng - Rahmawati; Darmayanti (MANDAILING GLOBAL EDUKASIA, 2025)
This research aims to improve students' ability to understand the material of faith to the last day through the application of the Problem Based Learning (PBL) learning model in grade VII students of SMP Negeri 3 Trienggadeng for the 2023/2024 Academic Year. The background of this research is the low understanding of students on the material of faith to the last day, which is shown from the pre-cycle average score of 60, below the Minimum Completeness Criterion (KKM) which is 70. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The research subjects amounted to 20 students, consisting of 12 women and 8 men. Data collection techniques include learning outcome tests, observation of teacher and student activities, and documentation. Data analysis was carried out qualitatively and quantitatively by comparing results between cycles. The results of the study showed a significant increase in student understanding. In the first cycle, the completion percentage reached 70% with 15 students completing it. In the second cycle, the percentage of completeness increased to 85% with 17 students complete. The activities of students and teachers also showed an increase from the good category to excellent. Thus, the application of the Problem Based Learning learning model has proven to be effective in increasing students' understanding of the material of faith to the last day at SMP Negeri 3 Trienggadeng.